Pediatric Nurses' performance enhancement regarding management of quality Sensitive nursing Indicator: Pediatric IV infiltration in intensive care units - Mona Ibrahim Abouzeid; Mohamed Gamal Elsehrawy; Maha Mahmoud Saadoon; Hanaa Mohamed Ibrahim Nassar; Ateya Megahed Ibrahim; Amal Sobhy Mahmoud; Nermen Abdelftah Mohamed; Hassanat Ramadan Abdel-Aziz; Mohamed A. El-Sakhawy; Eman SM Shahin (Elsevier, 2024)
Background: Intravenous complications, especially pediatric IV infiltration, are common in pediatric departments because such complications occur more frequently in children than in adults. Aim: To investigate the pediatric nurses' performance enhancement regarding the management of Pediatric IV infiltration. Subjects and Method: A quasi-experimental study was conducted. The study was carried out at Pediatric and Neonatal Intensive Care Units in Port Said Universal Health Insurance Hospitals. Data was collected from 50 pediatric nurses by using the Pediatric Nurses' Knowledge Assessment Questionnaire and an observational checklist schedule for nurses' practice before and after the implementation of an educational program regarding intravenous infiltration management. Results: No statistically significant relationship between pediatric nurses' knowledge before and after the program, while a statistically significant relation was evidenced between their practice before and after the program. Conclusion: the educational program was effective for pediatric nurses' performance by increasing their knowledge and improving their practice, with only a statistically significant difference between nurses' practice before and after the program. Recommendations: The educational program should be periodically conducted for pediatric nurses to enhance their performance to achieve high-quality nursing care for pediatric patients.